Quantifying the spatial flow of soil conservation service to optimize land-use pattern under ecological protection scenarios - Wang, Yudan; Liu, Xianfeng; Li, Jing; Wang, Yida; Bai, Jizhou; Zhou, Zixiang (Frontiers in Earth Science, 2022)
Land use pattern optimization is an effective approach for sustaining soil conservation service (SCS) under the influence of climate change and anthropogenic activities across the Loess Plateau. However, current studies established ecological protection scenarios (EPSs) for land-use optimization based on the transfer matrix of ecological protection scenario (EPS) alone, which ignores the important role of the scientific intervention by human beings on land-use patterns. To fill this knowledge gap, the Wuding River watershed was employed as the research object, and land use under three EPSs was simulated according to the transfer matrix, dry-wet zoning, slope, and soil erosion zoning. The quantity of SCS and its spatial flow and benefit under different climate scenarios were then simulated and compared with those under natural development scenarios (NDSs). SCS was found to decrease due to expansion of urban areas and agriculture under the NDSs and increase under the EPSs relative to the NDSs. In addition, under the EPSs, SCS restricted with dry-wet zoning exhibited no significant advantage over those without additional constraints. However, when complex constraints, such as dry-wet zoning, slope, and soil erosion zoning, were combined, SCS was significantly improved in areas with large topographic fluctuations. Further, compared with that in 2000‒2020, the benefit of SCS in future scenarios displayed an increasing trend along the direction of the mainstream. Owing to the cumulative benefit, when the spatial flow of the SCS upstream decreases with urban expansion, the benefit for the downstream area, which is provided by land-use optimization, will decrease. Overall, our findings provide a framework for land use optimization by incorporating ecosystem service flow, ultimately facilitating land management, ecological restoration, and soil erosion prevention.